2012
DOI: 10.1136/bjophthalmol-2012-302047
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visual acuity, higher-order aberrations and corneal asphericity after refractive lenticule extraction and wavefront-guided laser-assisted in situ keratomileusis for myopia

Abstract: In myopic eyes, FLEx induces significantly fewer ocular fourth-order aberrations than wfg-LASIK, possibly because it causes less oblation in the corneal shape, but there was no statistically significant difference in visual acuity or in the induction of third-order aberrations and total HOAs. It is suggested that FLEx is essentially equivalent to wfg-LASIK in terms of visual acuity and total HOA induction, although the characteristics of HOA induction are different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 29 publications
0
49
0
1
Order By: Relevance
“…25 [31]. Other reports on ReLEx smile [11,12,15,16] and 500-kHz ReLEx flex [17][18][19][20][21] have found very similar refractive outcomes in smaller numbers of patients.…”
Section: Refractive Outcomementioning
confidence: 81%
See 3 more Smart Citations
“…25 [31]. Other reports on ReLEx smile [11,12,15,16] and 500-kHz ReLEx flex [17][18][19][20][21] have found very similar refractive outcomes in smaller numbers of patients.…”
Section: Refractive Outcomementioning
confidence: 81%
“…In these studies, both ReLEx flex and LASIK were found to increase the total corneal or whole-eye HOAs; however, ReLEx flex induced less spherical aberration than LASIK. Furthermore, in LASIK the induced HOAs were found to increase with the degree of attempted refractive correction, whereas in ReLEx flex no such correlation was found [19]. Parallax error during excimer laser photoablation has been suggested as an explanation for the observed differences in induced spherical aberration after LASIK and ReLEx flex [19].…”
Section: Higher Order Aberrations (Hoas) and Contrast Sensitivitymentioning
confidence: 98%
See 2 more Smart Citations
“…2,3,[8][9][10][11][12][13][14] In one study on 279 eyes after SMILE, 0.4 % of eyes were reported to have a loss of two or more lines. 3 By contrast, a 2.4 % risk for a two-line loss was found in 670 eyes by Hjortdal et al 6 However, in the same study, a safety index (CDVA before/CDVA after surgery) of 1.07±0.22 was found, indicating that CDVA on average increased after surgery, as would be expected because of the image magnification of myopic keratorefractive procedures.…”
Section: Safetymentioning
confidence: 99%